PERTUMBUHAN DAN PRODUKSI JAGUNG MANIS (Zea mays sacaratha Sturt. L) PADA BERBAGAI JARAK TANAM DAN WAKTU OLAH TANAH - Evy Thyrida Silaban; Edison Purba; Jasmani Ginting (Universitas Sumatera Utara, 2013)
The aim of the research was to evaluate the growth and production of sweet corn (Zea mays sacharata Sturt. L) planted at various distance and land preparation (soil tillage prior to planting). The treatments were arranged in split plot design with three replication. The study consists of two factors, as main plot was time of soil tillage prior to planting (one and seven days) whereas sub plot was planting distance consist of four different spaces : 70cm x 10cm, 70cm x 20cm, 70cm x 30cm dan 70cm x 40cm. Result showed that the plant spacing consists of 70cm x 40cm performs significant effect on number of leaves, stem diameter, cob diameter, and production per plant, but not significant effect on flowering time and number of cobs per plot. The interaction between time of planting and planting space had no significant effect on plant height, number of leaves, stem diameter, days to flowering, cob diameter, number of cobs per plot, weight of cobs per plot and production per plant. Keywords: sweet corn, plant spacing and tillage time